I hope I die before I get old: The supply side of the market for suicide bombers - Thomas Apolte (Westfälische Wilhelms-Universität Münster, Centrum für Interdisziplinäre Wirtschaftsforschung (CIW), 2017)
We explore the supply side of the market for suicide bombers. While the strategic edge of suicide attacks for certain terrorist organizations has been thoroughly explored, the motivation of the suppliers remains quite mysterious. Following a review of existing theoretical approaches and empirical findings we develop a model of the supply of suicide bombing, the motivation of which is expressive but time inconsistent. The model implies terrorist organizations to provide a commitment device in exchange for the "services'' of those suicide bombers' that do not suffer from any mental or physical burden of life. By contrast, suicide attackers that do suffer from some sufficiently severe burden of life are not reliant on any commitment device and should therefore be expected to more frequently act as lonesome-wolf attackers.
Keywords: D74; D91; F52; H56; 330